Significantly Enhanced Synthesis of Aromatic Esters of Arbutin Catalyzed by Immobilized Lipase in Co-solvent Systems - Yang, Rongling; Nie, Zekun; Xu, Ningning; Zhao, Xiangjie; Wang, Zhaoyu; Luo, Hongzhen (Frontiers in Bioengineering and Biotechnology, 2020)
Highly efficient and regioselective synthesis of pharmacologically interesting aromatic esters of arbutin catalyzed by immobilized lipase from Penicillium expansum in co-solvent systems was successfully carried out. As compared to tetrahydrofuran solvent, the initial rate and substrate conversion of arbutin vanilylation were markedly enhanced in tetrahydrofuran-isopropyl ether (20%, v/v). Moreover, the effects of three reaction parameters (enzyme amount, temperature and substrate molar ratio of vinyl vanillic acid to arbutin) on 6′-O-vanilloyl-arbutin synthesis were scrutinized and the key process parameters were optimized using response surface methodology (RSM). The experimental data were fitted well to a second order polynomial model by using multiple regression analysis. The best combination of variables was 50°C, 93 U/mL and 11 for the reaction temperature, the enzyme amount and mole ratio of arbutin to vinyl vanilic acid, respectively, and which the reaction rate, substrate conversion and regioselectivity were as high as 8.2 mM/h, 93 and 99%. It was worth noting that a variety of aromatic esters of arbutin were obtained with much higher conversion (93–99%) at these optimal conditions.